(untitled) (ENTHYMEMA, 2020)
Interpretatio nominis was certainly one of Italo Calvino’s interests throughout his writer’s life, as witnessed by the different pseudonyms he adopted for himself over the years, the hermeneutic investigations he conducted about his name, and above all his arguments on the topic. Within the onomastic potential offered by If on a Winter’s Night a Traveler, the reader is struck by the accumulation of proper names that identify the characters: among these, some tell-tale names have been chosen at random. In the novel Calvino also maintains a dialogue with meta-onomastic, in harmony with the metanarrative orientation developed in the novel. Along the story, in fact, there are several considerations on the importance of nominatio. Calvino seems to tell us that everything revolves around the name because it is through it that we are recognized. It is therefore easy to conclude that the onomastic investigations can provide another way to delve into this novel.